If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(n + -1.8) = 2n + 1 Reorder the terms: 3(-1.8 + n) = 2n + 1 (-1.8 * 3 + n * 3) = 2n + 1 (-5.4 + 3n) = 2n + 1 Reorder the terms: -5.4 + 3n = 1 + 2n Solving -5.4 + 3n = 1 + 2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2n' to each side of the equation. -5.4 + 3n + -2n = 1 + 2n + -2n Combine like terms: 3n + -2n = 1n -5.4 + 1n = 1 + 2n + -2n Combine like terms: 2n + -2n = 0 -5.4 + 1n = 1 + 0 -5.4 + 1n = 1 Add '5.4' to each side of the equation. -5.4 + 5.4 + 1n = 1 + 5.4 Combine like terms: -5.4 + 5.4 = 0.0 0.0 + 1n = 1 + 5.4 1n = 1 + 5.4 Combine like terms: 1 + 5.4 = 6.4 1n = 6.4 Divide each side by '1'. n = 6.4 Simplifying n = 6.4
| 6(x-1)-2(2-x)=8-(2-6x) | | x^4+4x^3+5x^2+2x=0 | | q*(5-q)= | | 3y=-28-x | | 2(1+x)-1=3(2x+1)+2 | | z-48=-32 | | (5-q)-5q= | | 8x-1/5-1=(50-2x/9)+(3x+3/4) | | 16x+7x+15=0 | | 5-q= | | 10n=4 | | 5x-4=14x-13 | | 3x+26=10x-41 | | 20*(4x+1)-24(3x+1)=15*60-60*(25-x) | | 15x-176=6x-14 | | 24*(3x-1)-20*(5x+1)=120*(x+1)-3*120 | | 6y+(8)(7)-4=42 | | 11x+2=2x+128 | | 155-5x=40x+15x | | 7-10x=55-24x | | x^2+16x+9=18 | | 145-8x=8x+15 | | 182-6x=5x+24 | | 2x+96=9x-9 | | 81-5x=22x+21 | | 8-8x=68-36x | | 4x^2-12x-91=0 | | h=20+50t-16t^2 | | t+5=3t+5 | | 38-4x=5x+23 | | 11-8x=131-36x | | 124-7x=11x+24 |